2021
DOI: 10.21037/atm-20-6980
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of endovascular treatment for chronic total occlusion of the internal carotid artery

Abstract: The management of patients with symptomatic chronic total occlusion (CTO) of the internal carotid artery (ICA) is controversial. The aim of this systematic review was to investigate patient selection, technical success, early and late outcome of endovascular treatment for CTO of the ICA. PubMed/Medline and EMBASE databases were searched until January 2, 2020 for studies on endovascular treatment for CTO of the ICA. A descriptive analysis of demographic, clinical and anatomic data, endovascular technique, perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 37 publications
1
15
0
1
Order By: Relevance
“…Both hybrid surgery and EI can recanalize an occluded carotid artery with a low rate of neurological complications. The technical success rate of EI was 55%-70%, while that of hybrid surgery was significantly increased to 66.0%-98% (1,5). Despite these data, the assessment and treatment of patients with ICAO remain controversial.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both hybrid surgery and EI can recanalize an occluded carotid artery with a low rate of neurological complications. The technical success rate of EI was 55%-70%, while that of hybrid surgery was significantly increased to 66.0%-98% (1,5). Despite these data, the assessment and treatment of patients with ICAO remain controversial.…”
Section: Discussionmentioning
confidence: 99%
“…A multicenter, prospective, randomized controlled study indicated that symptomatic patients with CICAO did not benefit from extracranial-intracranial (EC-IC) artery bypass (4) Thus, carotid endarterectomy (CEA) and endovascular interventions (EI) are potential but challenging choices. Due to technical difficulty and unfavorable outcomes in early clinical trials, society guidelines failed to recommend carotid revascularization surgery for patients with CICAO (5,6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is difficult to judge the length of the lesion preoperatively, the possibility of distal extension should be considered. Some authors have suggested that the rate of success of recanalization can decrease with longer lesions [10] , [11] , [12] . Anzuini et al.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged attempts to pass through the lesion may also lead to complications. Myrcha and Gloviczki noted that if the lesion cannot be traversed within 30 minutes, the procedure must be halted [11] . Surgeons should be prepared for other methods, such as bypass surgery, in case recanalization fails.…”
Section: Discussionmentioning
confidence: 99%